Environmental Awareness as a Moderator of the Relationship between Green Packaging and Purchase Decision: An Empirical Investigation of Aqua Products in the Indonesian Market - Fatoni, Afif; Rifqy, Muhammad; Juniwati, Juniwati; Ramadania, Ramadania (Economic and Bussiness Faculty, Dr Soetomo University, 2025)
This study aims to examine the effect of green packaging on purchase decision, with environmental awareness as a moderating variable, in the context of Aqua bottled water products in Indonesia. Design/methodology/approach – The research model was tested using partial least squares structural equation modeling (PLS-SEM) with a sample of 200 Aqua consumers in Indonesia. The data were collected through an online survey and analyzed using WarpPLS software version 7.0. Findings – The results show that green packaging has a significant positive effect on purchase decision (β=0.533; P<0.001), and environmental awareness also significantly influences purchase decision (β=0.333; P<0.001). Furthermore, environmental awareness positively moderates the effect of green packaging on purchase decision (β=0.160; P=0.010). Research limitations – The study focused on a single brand in one product category in Indonesia, which may limit the generalizability of the findings. Future research can replicate the study in different contexts and explore other potential moderators. Practical implications – The findings suggest that green packaging is a strategic tool to attract environmentally conscious consumers. Companies should invest in sustainable packaging and communicate its benefits, especially to consumers with high environmental awareness. Originality/value – This study is the first to investigate the moderating role of environmental awareness on the effect of green packaging on purchase decision for Aqua products in Indonesia. It contributes to the green marketing literature and offers insights for sustainability practices.